Nikah Mut’ah (Kawin Kontrak ) Perbincangan Dari Perspektif Hadis Ahkam - Abdul Mukhsin (Jurnal Al-Muqaranah : Jurnal Perbandingan Hukum dan Mazhab, 2017)
Sexual problems are a reality that needs special attention and the problems that occurred throughout history. Sexual instincts for the good and welfare of humans. Among pernikahn provisions include those relating to the ability of a person in the economy, meaning that people who get married are primarily men he must have a good ability to relate carabao capability * with the spiritual and physical needs as well as that must be owned by both parties to responsibility as a consequence of a marriage   Kata kunci: Nikah, Mut`ah, Hadis ahkam, istinbath.